FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA KEUANGAN BANK UMUM YANG TERDAFTAR DI BEI (Students' Journal of Accounting and Banking, 2015)
The purpose of this reseach is to examine influence of Loan to Deposit Ratio, Earning Assets Quality, Good Corporate Governance, Net Interest Margin, Operating Expense to Operating Income, Capital Adequacy Ratio, Company Size, and BI Rate through Return On Assets of public banking listed at Indonesian Stock Exchange during 2011-2013. Population of this research are Commercial Bank that registered in Indonesian Stock Exchange from 2011 till 2013. Data on this research are coming from Indonesian Stock Exchange (BEI) and Financial Services Authority of Indonesia (OJK). Sample are choosen by purposive sampling method at least 27 company. Data’s test technique by using multiple linear regression analyze. The results showed that the Good Corporate Governance and Net Interest Marginhas a positive effect on Return On Assets. Operating Expenses to Operating Income and Company Size negatively effect the Return On Assets. While the Loan to Deposit Ratio, Earning Assets Quality, Capital Adequacy Ratio, and BI Rate has no effect on Return On Assets. Keywords: Loan to Deposit Ratio, Earning Assets Quality, Good Corporate Governance, Net Interest Margin, Operating Expense to Operating Income, Capital Adequacy Ratio, Company Size, and BI Rate Through Return On Assets